Bringing Space into the Classroom: An AR-Integrated E-Book on the Solar System for Students in Elementary School - Dinne Nursyaidah; Diana Rochintaniawati; Nanang Winarno; Rizky Agassy Sihombing (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an Augmented Reality (AR)-integrated e-book on solar system material to support science education. The development process followed five stages: Analysis, Design, Development, Implementation, and Evaluation. The e-book was validated by experts, yielding a score of 93.36%, indicating it is highly feasible for use in educational settings. Student responses were also assessed, with a score of 88.23%, categorizing the e-book as "very good." Key features of the AR-integrated e-book include enhanced object visualization, allowing students to explore the solar system in greater detail, and interactive elements that encourage active participation in the learning process. These features help improve students' conceptual understanding and engagement with the material. The results suggest that the AR-integrated e-book is an effective educational tool, offering a modern approach to teaching solar system content. By incorporating AR technology, the e-book creates an immersive and engaging learning experience that enhances both comprehension and student involvement. The study concludes that this AR-based e-book is a valuable resource for science education, particularly for teaching complex subjects like the solar system, and has the potential to be applied effectively in various educational contexts.